Improving oral health knowledge for little dentists at elementary school level in Kartasura District - Dendy Murdiyanto; Ariyani Faizah; Nilasary Rochmanita Suparno; Septriyani Kaswindiarti; Juwita Raditya Ningsih; Dwi Kurniawati (Universitas Muhammadiyah Magelang, 2022)
Dental and oral health problems, especially dental caries, are a disease that affects almost half of the world's population. The largest proportion of dental health problems in Indonesia is dental caries. The predisposing factors for dental caries are knowledge and behavior. Usaha Kesehatan Gigi Sekolah (UKGS) in elementary schools is needed in an effort to increase knowledge and awareness of dental and oral health. The problems faced by SD/MI Kartasura are that UKGS activities have not been running continuously and the lack of facilities and infrastructure to support dental and oral health programs. Solutions to increase dental and oral health knowledge for little dentists at elementary school the method of implementing activities includes identifying partner problems (surveys), making starter kits for little dentists, making educational media, training little dentists and accompanying teachers, implementing routine programs by little dentists, monitoring and evaluation. This activity is able to increase the knowledge of little dentists in maintaining dental and oral health.